Uji Daya Hasil Galur Jagung Manis Varietas MS-UNSIKA (Zea mays L. saccharata Sturt.) Generasi M7 di Karawang - Aripin, Muhammad Fadli Futuhal; Syafi'i, Muhammad; Samaullah, Muhammad Yamin (JURNAL AGROPLASMA, 2023)
Sweet corn is a horticultural crop that is in great demand by the people of Indonesia. The need for sweet corn continues to increase. Seed varieties with low quality and quality lead to low production yields. Efforts to increase the production of sweet corn include the use of superior varieties. To obtain superior varieties, several lines can be tested by crossing and mutation methods using gamma-ray irradiation. This study aims to obtain the best lines in the MS-UNSIKA variety M7 sweet corn. The research was conducted in November 2022 – February 2023 on land owned by PT. Corteva Agriscience, Ciwaringin Village, Lemahabang District, Karawang Regency. The research method used was an experimental method using a single factor Randomized Block Design (RBD). There were 13 treatments and repeated 3 times so that there were 36 experimental plots consisting of treatments SR1, SR3, SR4, SR5, M6, M8, M9, M10, G11, G12, G13, G14, and G15. If there is a significant effect, further analysis of the DMRT (Duncan Multiple Range Test) is carried out at the 5% level. The results showed that the best average in the treatment of the SR1 strain variety MS-UNSIKA included cob weight with husks 283.00 grams, cob weight without husks 249.50 grams, cob length 20.45 cm, cob diameter 48.00 mm, number of row of 18 seeds, weight of 100 seeds 0.98 gram and yield of 6.80 kg/plot.